Kinesin-dependent transport results in polarized migration of the nucleus in oocytes and inward movement of yolk granules in meiotic embryos - McNally, Karen L. (2009)
During female meiosis, meiotic spindles are positioned at the oocyte cortex to allow expulsion of chromosomes into polar bodies. In C. elegans, kinesin-dependent translocation of the entire spindle to the cortex precedes dynein-dependent rotation of one spindle pole toward the cortex. To elucidate the role of kinesin-1 in spindle translocation, we examined the localization of kinesin subunits in meiotic embryos. Surprisingly, kinesin-1 was not associated with the spindle and instead was restricted to the cytoplasm in the middle of the embryo. Yolk granules moved on linear tracks, in a kinesin-dependent manner, away from the cortex, resulting in their concentration in the middle of the embryo where the kinesin was concentrated. These results suggest that cytoplasmic microtubules might be arranged with plus ends extending inward, away from the cortex. This microtubule arrangement would not be consistent with direct transport of the meiotic spindle toward the cortex by kinesin-1. In maturing oocytes, the nucleus underwent kinesin-dependent migration to the future site of spindle attachment at the anterior cortex. Thus the spindle translocation defect observed in kinesin-1 mutants may be a result of failed nuclear migration, which places the spindle too far from the cortex for the spindle translocation mechanism to function.